Trait mindfulness is associated with enhanced daily affectivity and cognition independent of daily stressors exposure: Insights from large-scale daily diary studies in the US and Singapore - CHUA, Yi Jing (Institutional Knowledge at Singapore Management University, 2025)
Trait mindfulness has been linked to various adaptive outcomes, including attenuated affective and cognitive responses to laboratory-induced stress. However, the role of trait mindfulness as a resilience factor against daily stressors exposures is less established. Across 2 studies, multilevel analysis was used to examine the relationships between trait mindfulness and daily affect and cognition, as well as affective and cognitive reactivity to and recovery from everyday stressor exposure. Trait mindfulness was significantly associated with higher daily positive affect in both studies, lower negative affect and cognitive failure, and lower cognitive reactivity to daily stressor exposure in Study 2. However, trait mindfulness did not attenuate cognitive reactivity in Study 1, nor affective reactivity to daily stressor exposure and affective and cognitive recovery from previous-day stressor exposure in both studies. Overall, results suggest that the mechanisms underlying the affective and cognitive buffering effect of trait mindfulness are not stress specific.